Detrital zircon geochronology of the Carboniferous Baixo Alentejo Flysch Group (South Portugal); constraints on the provenance and geodynamic evolution of the South Portuguese Zone - Rodrigues, B. (2015)
U–Pb detrital zircon data from the Baixo Alentejo Flysch Group in the South Portuguese Zone show significant age differences between formations. The Visean Mértola Formation and Serpukhovian to early Bashkirian Mira Formation are dominated by zircons in the 316–388Ma age range, whereas the late Bashkirian to late Moscovian Brejeira Formation is dominated by zircons with an age range of 498–687Ma. Detrital zircons spanning an age range of 0.9–1.1Ga are present in the Brejeira Formation but are absent in the Mértola and Mira formations. Detrital zircon ages of the Mértola and Mira formations indicate provenance from an extra-basinal source (Ossa–Morena Zone) with a minor intra-basinal contribution (South Portuguese Zone). The abundant presence of detrital zircon with age ranges of 500–750 and 0.9–1.1Ga in the Brejeira Formation suggests a sediment source from the Avalon–Meguma terranes with limited recycling from the SW Portugal Domain. The different inferred source areas for the Baixo Alentejo Flysch Group formations are attributed to the presence of a forebulge that was formed in Mid-Visean times during the foreland phase of the South Portuguese Zone. The forebulge acted as a physical barrier separating sub-basins that accumulated the Mértola–Mira and Brejeira sediments respectively.